2020
DOI: 10.3390/ijerph17186717
|View full text |Cite
|
Sign up to set email alerts
|

Safety Climate Perceptions in the Construction Industry of Saudi Arabia: The Current Situation

Abstract: Workers’ wellbeing and safety is important in the construction industry due to the high risk of accidents. Safety climate development is a positive initial step toward raising the safety levels of construction practitioners. This study aims at revealing the factors influencing safety climate perceptions in the construction industry of Saudi Arabia. A set of extracted factors from the literature was validated and used to design a comprehensive questionnaire survey. Data was collected from 401 personnel working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 97 publications
(65 reference statements)
2
28
0
Order By: Relevance
“…As far as the practical assessment of the above items is concerned, the use of a Likert scale to state the level of agreement of the respondents was the common method in the selected studies, usually adopting a 5-point scale ranging from 1 (never) to 5 (always) in case of direct questions or 1 (totally disagree) to 5 (totally agree) in case of statements. Furthermore, it is worth mentioning that the analysis of psychological elements, such as the subjective assessment of safety that can be derived by the SC measurement, contributes to determine also the safety culture status among the interviewed workers [ 17 , 61 ]. Based on this, echoing Westaby and Lee [ 62 ], Arcury and colleagues [ 43 , 53 ] have investigated SC among different groups of farmers to understand their work safety culture level, which encompasses behavioral, situational, and psychological elements of safety.…”
Section: Background Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As far as the practical assessment of the above items is concerned, the use of a Likert scale to state the level of agreement of the respondents was the common method in the selected studies, usually adopting a 5-point scale ranging from 1 (never) to 5 (always) in case of direct questions or 1 (totally disagree) to 5 (totally agree) in case of statements. Furthermore, it is worth mentioning that the analysis of psychological elements, such as the subjective assessment of safety that can be derived by the SC measurement, contributes to determine also the safety culture status among the interviewed workers [ 17 , 61 ]. Based on this, echoing Westaby and Lee [ 62 ], Arcury and colleagues [ 43 , 53 ] have investigated SC among different groups of farmers to understand their work safety culture level, which encompasses behavioral, situational, and psychological elements of safety.…”
Section: Background Analysismentioning
confidence: 99%
“…Therefore, given the importance of focusing on human-centered approaches to enhance safety management [ 15 ], numerous studies have investigated SC in different types of industry [ 2 ], for example the construction sector [ 16 , 17 ], as well as the mining, oil and gas extraction [ 8 , 18 , 19 ], healthcare [ 20 ], fire service [ 21 ], and aviation [ 22 ] sectors. However, when it comes to agricultural activities, very little research can be found addressing SC, although agriculture is deemed to be a very hazardous working environment [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The general background of workers' knowledge, training, qualification, and skills. 1 Source: Mosly and Makki [37]. 2 Factors are ranked based on the significance of their correlations with the overall safety climate, as perceived by construction site personnel.…”
Section: Competencementioning
confidence: 99%
“…Three studies were previously conducted to explore different aspects of safety climate perceptions among construction workers in Saudi Arabia. The first study determined the current situation and identified a set of 13 factors influencing the safety climate in the construction industry of Saudi Arabia [ 37 ]. The second study revealed that the 13 factors act as determinants of safety climate in construction sites of Saudi Arabia under three key components of safety climate which are safety commitment, safety interaction, and safety support [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…These high casualty rates reflect the poor safety performance in the construction industry around the world [ 6 , 7 ], which has become a significant public health problem. Therefore, it is essential to improve occupational health and safety as well as safety performance in the industry [ 8 ]. Many studies have been performed to investigate the key factors in determining construction safety performance, and current research has reached a consensus that the safety performance of construction projects is the result of the interactions between the contractor’s internal safety investment and the government’s external safety supervision [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%